Deterrent activities in the crude lipophilic fractions of Antarctic benthic organisms: chemical defences against keystone predators - Núñez-Pons, Laura; Avila, Conxita (Polar Research, 2014)
Generalist predation constitutes a driving force for the evolution of chemical defences. In the Antarctic benthos, asteroids and omnivore amphipods are keystone opportunistic predators. Sessile organisms are therefore expected to develop defensive mechanisms mainly against such consumers. However, the different habits characterizing each predator may promote variable responses in prey. Feeding-deterrence experiments were performed with the circumpolar asteroid macropredator Odontaster validus to evaluate the presence of defences within the apolar lipophilic fraction of Antarctic invertebrates and macroalgae. A total of 51% of the extracts were repellent, yielding a proportion of 17 defended species out of the 31 assessed. These results are compared with a previous study in which the same fractions were offered to the abundant circum-Antarctic amphipod Cheirimedon femoratus. Overall, less deterrence was reported towards asteroids (51%) than against amphipods (80.8%), principally in sponge and algal extracts. Generalist amphipods, which establish casual host–prey sedentary associations with biosubstrata (preferentially sponges and macroalgae), may exert more localized predation pressure than sea stars on certain sessile prey, which would partly explain these results. The nutritional quality of prey may interact with feeding deterrents, whose production is presumed to be metabolically expensive. Although optimal defence theory posits that chemical defences are managed and distributed as to guarantee protection at the lowest cost, we found that only a few organisms localized feeding deterrents towards most exposed and/or valuable body regions. Lipophilic defensive metabolites are broadly produced in Antarctic communities to deter opportunistic predators, although several species combine different defensive traits. Keywords: Antarctic invertebrates; Antarctic algae; chemical ecology; sea star Odontaster validus; amphipod Cheirimedon femoratus; chemical defence.
Keywords: Antarktis; alger; kjemisk økologi; virvelløse dyr